Effect of alpha-tocopherol on superoxide radical and toxicity of cadmium exposure - Novelli, JLVB; Novelli, ELB; Manzano, M. A.; Lopes, A. M.; Cataneo, A. C.; Barbosa, L. L.; Ribas, B. O. (Carfax Publishing, 2000)
Contamination with cadmium compounds poses high potential risk for the health of populations and for this reason the treatment of their toxic effects should urgently be established. The present study was carried out to determine whether or-tocopherol intake can protect tissues against damage induced by cadmium, and to clarify the contribution of superoxide radicals (O-2(-)) in this process. Cadmium chloride was tested for tissue damage by a single intraperitoneal injection of Cd2+ ions (2 mg Kg(-1)). To determine the potential therapeutic effect of Vitamin E, a group of Cd2+-treated rats received a drinking solution of or-tocopherol (40 mg l(-1)) for 15 days. Cadmium induced increased serum creatinine and total lactate dehydrogenase, reflecting renal and cardiac damage. The increased lipoperoxide and decreased Cu-Zn superoxide dismutase levels indicated the generation of superoxide radicals in cadmium-treated rats. Tocopherol induced increased serum high-density lipoprotein and depressed the toxic effects of Ca2+ alone, since creatinine and lactate dehydrogenase determinations were recovered to the control values. Tocopherol decreased lipoperoxide and led the superoxide dismutase activities to approach those of the control values. We concluded that superoxide radicals are produced as mediators of cadmium toxicity. Tocopherol possesses a significant anti-radical activity and inhibits the cadmium effect on superoxide dismutase activity. Tocopherol also protected tissues from the toxic effects of cadmium by a direct antioxidant action which decreased lipoperoxide formation.
Keywords: cadmium; alpha-tocopherol; superoxide radical; antioxidant; rats